UNIMAS Students' Perception of the Use of Roleplay as an Assessment in Increasing Communicative Competence and Social Constructivism: An Action Research - Abang Ahmad, Dayang Hartijah (Trends in Undergraduate Research, 2024)
Roleplay or simulation are classroom activities that provide students with a 'safe' and less threatening environment for learning. In ESL for higher educational institutions, roleplay is used as one of the assessment strategies because of its authenticity and practicality. This study examined students' perception of roleplay to increase their communicative competence and social constructivism. One hundred eight participants from various faculties at Universiti Malaysia Sarawak (UNIMAS) were chosen using the purposive sampling method as the study's participants. SPSS 2.0 was used as the instrument, and several tests (T-test, F-test, Pearson) were conducted to obtain the results. The findings showed that 1) using roleplay as an assessment has increased their communicative competence; 2) the student’s gender does not affect the students' roleplay and social constructivism; 3) the student’s study programmes do not affect their roleplay and social constructivism, and 4) social constructivism appears to have a strong relationship with roleplay based on the positive correlation result. This study has shown that roleplay is an effective tool for ESL classrooms as it allows students to express themselves confidently, practise conversational English, and improve their communicative competence and social constructivism.